GAMBARAN KEPUTUSAN PERENCANAN KARIER SISWA SMKN 9 GARUT - Beni Heriyanto; Ika Mustika; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Research on the decision description about the career of students of SMKN 9 Garut is a descriptive quantitative study with the aim of obtaining an overview of the level of career planning of students at SMKN 9 Garut. Based on the research results, it is found that career planning decisions at SMKN 9 Garut are in the high category on each indicator, which consists of I believe that the goal is; involved in information seeking; and select interests in further education and employment. This illustrates that students have: optimism in the continuing education and employment database, a desire to collect information that supports further education and employment, and a tendency to determine further education or employment. Keywords:Career Decisions, Vocational School Students